The living world - Seddon, Tony; Bailey, Jill. (Garden City, N.Y. : Doubleday, 1986)
Presents snippets of lesser-known information about plants and animals.
Includes index and bibliography : pages 150-151.
Keywords: Biology -- Juvenile literature; Life (Biology) -- Juvenile literature; Animals -- Miscellanea; Plants -- Miscellanea